Efficiency of Health Centers in Cambodia: Case Study in Takeo Province - Pelissier, Aurore; Mathonnat, Jacky (IDEAS Working Paper Series from RePEc, 2015)
Financing and efficiency of primary health care are two major issues for the development and deepening of health universal coverage in a context of strong financial constraint. In Cambodia, the development of demandside financing schemes - Health Equity Fund and Community-Based Health Insurance ? provides an opportunity to enhance the health centers (HCs) activity and thus their performance, which are very low as underlined by the literature. Nevertheless, except our study, the literature on Cambodian HCs focuses on the analysis of their activity and financing without taking into consideration efficiency issues. From a field survey, our study is a contribution to fill this gap by estimating with a data envelopment analysis the technical efficiency of HCs in the rural province of Takeo for 51 HCs observed over the period 2008 to 2010. This study assesses the overall weak efficiency of HCs. Conclusions emphasize the potential role of demand-side financing schemes development and highlight important policy implications for demand and supply sides of health care in Cambodia.